2008
DOI: 10.1021/ma702272e
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Fractionation and Isothermal Crystallization of Polyethylene Nanocomposites Prepared by in Situ Polymerization

Abstract: Nanocomposites of high-density polyethylene (HDPE) and carbon nanotubes (CNT) of different geometries (single wall, double wall, and multiwall; SWNT, DWNT, and MWNT) were prepared by in situ polymerization of ethylene on CNT whose surface had been previously treated with a metallocene catalytic system. In this work, we have studied the effects of applying the successive self-nucleation and annealing thermal fractionation technique (SSA) to the nanocomposites and have also determined the influence of compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 48 publications
11
80
0
1
Order By: Relevance
“…The decrease of the dielectric strength (reduction of the relaxing material) is caused by crystal formation due to the progressive transfer of the amorphous material to the growing crystalline phase [34,[56][57][58]. For neat PTT and PTT/MWCNTs nanocomposites it is observed a decrease in the intensity of the !-relaxation process, characterized by the value of the dielectric loss at the maximum ($# max ) and a positional shift of the maximum of the !-relaxation towards lower frequencies with increasing crystallization time in agreement with previous results [55][56][57][58]. [58].…”
Section: Effect Of Mwcnts On Cold Crystallization Of Ptt Nanocompositessupporting
confidence: 92%
See 2 more Smart Citations
“…The decrease of the dielectric strength (reduction of the relaxing material) is caused by crystal formation due to the progressive transfer of the amorphous material to the growing crystalline phase [34,[56][57][58]. For neat PTT and PTT/MWCNTs nanocomposites it is observed a decrease in the intensity of the !-relaxation process, characterized by the value of the dielectric loss at the maximum ($# max ) and a positional shift of the maximum of the !-relaxation towards lower frequencies with increasing crystallization time in agreement with previous results [55][56][57][58]. [58].…”
Section: Effect Of Mwcnts On Cold Crystallization Of Ptt Nanocompositessupporting
confidence: 92%
“…The topological confinement of macromolecular chains at their interfaces and strong interactions between them can increase of supercooling. Recent study on crystallization behaviour of nanocomposites based on high density polyethylene and CNTs performed by Müller and coworkers [54,55] have shown that in nanocomposites a competition between super-nucleation and confinement occur. At low contents the nucleation effect dominates.…”
Section: Effect Of Mwcnts Addition On Thementioning
confidence: 99%
See 1 more Smart Citation
“…129 However, another study, also with metallocene-grafted HDPE, found a significant increase in the crystallization rate while also finding a substantial decrease in the Avrami exponent n. This study also found significantly thicker crystals as measured by a successive self-nucleation and annealing thermal fractionation technique performed in a DSC. 260 Both studies found that the fractional crystallinity initially increased to $10% nanotube content, then decreased as the nanotube content increased above 10%. Studies on covalently bonded polycaprolactone and polyethylene oxide also found a significant increase in overall crystallization rate with essentially no decrease in n in the former case and a decrease in the latter case.…”
Section: Semicrystalline Polymersmentioning
confidence: 98%
“…Some techniques were using compatibilizer such as PP-g-MA [6], in-situ polymerization of polyolefin with CNT [7,8], and by modification of the CNT's surface [9].…”
Section: Introductionmentioning
confidence: 99%